No Brainer - Kinney, Jeff (UK Penguin Random House Children's UK, 2023)
Up until now, middle school hasn't exactly been a joyride for Greg Heffley. So when the town threatens to close the crumbling building, he's not too broken up about it. But when Greg realizes this means he's going to be sent to a different school than his best friend, Rowley Jefferson, he changes his tune. Can Greg and his classmates save their school before it's shuttered for good? Or is this the start of a whole new chapter for Greg?
In No Brainer, book 18 of the Diary of a Wimpy Kid series from #1 international bestselling author Jeff Kinney, it's up to Greg to save his school before it's shuttered for good.